2005
DOI: 10.1007/s10886-005-8398-8
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Tartrate Crystals in the Midgut of the Grape Leafhopper

Abstract: Calcium tartrate crystals were observed in the midgut of grape leafhoppers. This unique compound was found for the first time in insects. The size of the crystals varied strongly between and within individuals with a mean length of 153 +/- 87 microm and a mean width of 71 +/- 46 microm. In addition, the number of crystals per individual showed a broad variation and ranged from 1 to 150 crystals/individual. The occurrence of calcium tartrate crystals as well as the number of crystals per individual followed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Therefore, the possibility of TA being synthesized and stored in the cell as an alternative defensive mechanism, should also be considered at the whole organism level. The potential role in defense against herbivores was suggested by Böll et al (2005), who found evidence of calcium tartrate crystals in the midgut of the phloem-sucking grape leafhoppers (Empoasca vitis) after feeding on grapevine leaves, with levels increasing during ripening of berries of the vine. Although TA was ineffective at preventing leafhoppers from eating the grapevine leaves, calcium tartrate crystals may have a more toxic effect on other insects that feed on grapevine.…”
Section: Other Potential Roles Of Ta Biosynthesismentioning
confidence: 98%
“…Therefore, the possibility of TA being synthesized and stored in the cell as an alternative defensive mechanism, should also be considered at the whole organism level. The potential role in defense against herbivores was suggested by Böll et al (2005), who found evidence of calcium tartrate crystals in the midgut of the phloem-sucking grape leafhoppers (Empoasca vitis) after feeding on grapevine leaves, with levels increasing during ripening of berries of the vine. Although TA was ineffective at preventing leafhoppers from eating the grapevine leaves, calcium tartrate crystals may have a more toxic effect on other insects that feed on grapevine.…”
Section: Other Potential Roles Of Ta Biosynthesismentioning
confidence: 98%
“…These compounds are thought to either bind to or eliminate excess calcium or, in the case of CaOx, to neutralize and eliminate the oxalic acid. 38,39 Calcium salts have also been reported to be present in the shells of eggs of various insects, adding to their rigidity. Whereas other calcium salts such as calcium carbonate, calcium urate, or CaOx that have been observed in a variety of insects usually occur in the Malpighian tubules, calcium tartrate crystals have been identified in the midgut of the grape leafhopper.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of calcium salts in the midgut of insects has been detected only in rare cases. 39,40 The primary excretory organs of insects are the Malpighian tubules and the rectum. The blind-ended Malpighian tubules empty into the intestinal tract at the midgut/hindgut junction.…”
Section: Discussionmentioning
confidence: 99%